Sufistic Self-healing: The Intersection of Sufism and Psychology - Hidayati, Laily; Fatimah, Siti (Proceedings of International Conference on Muslim Society and Thought, 2024)
Humans always desire to know themselves, know the world around them, and know their place in the world. This search has taken humanity from religious dogmas to philosophical discourse and the empirical sciences. Although human civilization has progressed in various alternatives for understanding the self about nature, the answers remain elusive. Spirituality, whether related to a particular religion or another, has been practiced for a long time and is claimed to provide answers to “unresolved doubts” (S. Haque Nizamie, et al, 2013). In recent years, there has been an increase in interest in spirituality, and advances in neuroscience have provided an opening to understand it from a more scientific viewpoint and place it in the proper perspective. In various cultures, spirituality is an important part of the belief system of the majority of society. This affects mental well-being and understanding of mental illness in terms of etiology, meaning, and self-healing modalities. It seems important for mental health professionals to be aware of how spirituality influences the mental well-being of individuals in both health and illness. This paper will outline the basic foundations of Sufism, how Sufism affects the mental well-being of individuals associated with it, and its relationship with psychology.